Bidirectional Relationship between Gastric Emptying and Plasma Glucose Control in Normoglycemic Individuals and Diabetic Patients - Bogdan Mircea Mihai; Cătălina Mihai; Cristina Cijevschi-Prelipcean; Elena-Daniela Grigorescu; Mihaela Dranga; Vasile Drug; Ioan Sporea; Cristina Mihaela Lăcătușu (Journal of Diabetes Research)
Gastric emptying and glycemic control pathways are closely interrelated processes. Gastric chyme is transferred into the duodenum with velocities depending on its solid or liquid state, as well as on its caloric and nutritional composition. Once nutrients enter the intestine, the secretion of incretins (hormonal products of intestinal cells) is stimulated. Among incretins, glucagon-like peptide-1 (GLP-1) has multiple glycemic-regulatory effects that include delayed gastric emptying, thus triggering a feedback loop lowering postprandial serum glucose levels. Glycemic values also influence gastric emptying; hyperglycemia slows it down, and hypoglycemia accelerates it, both limiting glycemic fluctuations. Disordered gastric emptying in diabetes mellitus is understood today as a complex pathophysiological condition, with both irreversible and reversible components and high intra- and interindividual variability of time span and clinical features. While limited delays may be useful for reducing postprandial hyperglycemias, severely hindered gastric emptying may be associated with higher glycemic variability and worsened long-term glycemic control. Therapeutic approaches for both gastric emptying and glycemic control include dietary modifications of meal structure or content and drugs acting as GLP-1 receptor agonists. In the foreseeable future, we will probably witness a wider range of dietary interventions and more incretin-based medications used for restoring both gastric emptying and glycemic levels to nearly physiological levels.